2002
DOI: 10.1097/00007632-200202150-00003
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Use of Corticosteroid and Bupivacaine Combination in Lumbar Disc Surgery

Abstract: It is concluded that the perioperative use of bupivacaine and corticosteroids during lumbar discectomy maintains effective postoperative analgesia and decreases opioid usage without complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
75
2
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 105 publications
(82 citation statements)
references
References 16 publications
2
75
2
3
Order By: Relevance
“…The results are in keeping with the local application of corticosteroid at the surgical site following lumbar discectomy. 21,22 In contrast to the findings from our study, intrathecal administration of corticosteroids in a rat model has been shown to have a mild effect on nociceptor-driven spinal sensitization. 14 One possible explanation for this different response to neuraxial steroid administration is that the dose of methylprednisolone and triamicinolone in a rat model was insufficient to prevent the nociceptor-driven spinal sensitization.…”
Section: (D1) Group 3 (D2) (N = 30) (N = 30) (N = 30) Vas (Rest) Vas contrasting
confidence: 99%
“…The results are in keeping with the local application of corticosteroid at the surgical site following lumbar discectomy. 21,22 In contrast to the findings from our study, intrathecal administration of corticosteroids in a rat model has been shown to have a mild effect on nociceptor-driven spinal sensitization. 14 One possible explanation for this different response to neuraxial steroid administration is that the dose of methylprednisolone and triamicinolone in a rat model was insufficient to prevent the nociceptor-driven spinal sensitization.…”
Section: (D1) Group 3 (D2) (N = 30) (N = 30) (N = 30) Vas (Rest) Vas contrasting
confidence: 99%
“…Several other reports also suggested the efficacy of local or systemic steroids in the immediate postoperative period. In various studies [6,9,13,14], saline or salinesoaked fat graft or absorbable gel was used in the control group and the effects were recorded. However in clinical practice we never inject saline or saline-soaked fat graft or Gelfoam if we do not intend to apply a local steroid or other agents.…”
Section: Discussionmentioning
confidence: 99%
“…Perioperative use of corticosteroids and bupivacaine [6][7][8][9]14] has been reported as effective analgesia and decreases opioid or analgesic use without complications. Local or systematic use of various steroids [1,13] is described in the literature in lumbar disc patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They relive pain by reducing inflammation and blocking transmission of nociceptive c-fibres and by suppressing ectopic neural discharge [9]. Some study demonstrated the analgesic effect of systemic corticosteroid in combination with bupivacaine [10][11][12].…”
Section: Introductionmentioning
confidence: 99%